Prevalência e fatores associados a dor crônica e doenças crônicas não transmissíveis em uma comunidade universitária - GONÇALVES, Camilla Silva (2019)
Objective: To estimate the prevalence and factors associated with chronic pain and non-communicable chronic diseases in the university population of the Federal University of Maranhão (UFMA), Bacanga campus. Materials and methods: This is a cross-sectional study with 1,960 participants, including students and servers. For data collection we used an online questionnaire (MAFIS) composed of 97 questions. Data were analyzed using the SPSS version 23.0 statistical program using absolute and relative frequencies. In order to verify the factors associated with DC and NTCD, we used the Chi-square test with subsequent mounting of the logistic regression model. was 5%.. Results: Most were female 60.6%, predominance of brown 52.5%, single 60.8% and aged between 18 to 25 years. As for risk factors, 85% say no smoking, 60.4% do not drink alcohol, 50% say sleep up to 6 h, more than half were considered inactive and insufficiently active, as for stress level 79.7% report having some degree of stress and eating habits corresponded between good and great with 78.8%. It was noted a high prevalence of CD in the university community of 80.6%, while for the presence of some CNCD only 28.8%. When compared between students and servers, pain had a prevalence of 80.4% and 83.1% respectively, and NCDs 28.2% for students and 36.6% among servers. Only the sex variable was associated with CD, and the following were: skin color, age and stress level. Regarding the routine impacts caused by CD and NTCD, it was shown that gender, physical activity level and stress level are associated. Discussion: As for the presence of pain as women were more likely to use some kind of pain, as well as for NCDs, or females showed a significant difference when compared to males. An age associated with NCDs, ages 18 to 25, is more likely to suffer from chronic illness, as people who consider themselves "stressed" are 21 times more likely to use NCDs. Those who automatically relate to "little" or "very" like to practice AF are protected from the presence of DCNT, compared to those who do not like to practice AF.Conclusion: The results show us a high prevalence of CD in the university community, and the most prevalent risk factor among those who made up Lifestyle is the Stress Level. Thus one should think of policies and programs that serve this population bringing well-being and health.